Synthesis and Properties of the Arrays of Magnetically Functionalized Carbon Nanotubes - Labunov, Vladimir; Prudnikava, Alena; Yanushkevich, Kazimir; Basaev, Aleksander; Danilyuk, Alexander; Fedotova, Yulia; Shulitskii, Boris (IntechOpen, 2011)
None